2013
DOI: 10.1371/journal.pone.0076720
|View full text |Cite|
|
Sign up to set email alerts
|

Serial Plasma Choline Measurements after Cardiac Arrest in Patients Undergoing Mild Therapeutic Hypothermia: A Prospective Observational Pilot Trial

Abstract: ObjectiveCholine is related to phospholipid metabolism and is a marker for global ischaemia with a small reference range in healthy volunteers. The aim of our study was to characterize the early kinetics of plasma free choline in patients after cardiac arrest. Additionally, we investigated the potential of plasma free choline to predict neurological outcome.MethodsTwenty patients admitted to our medical intensive care unit were included in this prospective, observational trial. All patients were enrolled betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The augmented utilization of phosphocholine for repairing the damaged cells/organelles under severe oxidative and systemic inflammatory condition should also lead to decrease in total Cho. On the other hand, in hypoxic states choline is released from hypoxic tissue into the plasma, thus increasing the basal circulating levels (Storm et al 2013). The efficient source of choline is phosphatidylcholine hydrolysis (Fagone and Jackowski 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The augmented utilization of phosphocholine for repairing the damaged cells/organelles under severe oxidative and systemic inflammatory condition should also lead to decrease in total Cho. On the other hand, in hypoxic states choline is released from hypoxic tissue into the plasma, thus increasing the basal circulating levels (Storm et al 2013). The efficient source of choline is phosphatidylcholine hydrolysis (Fagone and Jackowski 2013).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Storm et al . suggested that the plasma choline levels decreased 6–12 hours after the return of spontaneous circulation and reached a subnormal concentration, with a median of 4.0 μmol/L 35 . Until now, no reports have described the use of prepared samples in which the blood collection tubes were kept on ice prior to centrifugation.…”
Section: Discussionmentioning
confidence: 99%